2017
DOI: 10.1016/j.neuron.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The Anterior Insular Cortex→Central Amygdala Glutamatergic Pathway Is Critical to Relapse after Contingency Management

Abstract: Summary Despite decades of research on neurobiological mechanisms of psychostimulant addiction, the only effective treatment for many addicts is contingency management, a behavioral treatment that uses alternative non-drug rewards to maintain abstinence. However, when contingency management is discontinued, most addicts relapse to drug use. The brain mechanisms underlying relapse after cessation of contingency management are largely unknown, and until recently, an animal model of this human condition did not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
155
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(174 citation statements)
references
References 94 publications
(158 reference statements)
15
155
2
2
Order By: Relevance
“…There was a near‐significant decrease in BLA Arc immunoreactivity after guanfacine, which is consistent with previous research using in vivo electrophysiology and clonidine in the BLA . The CeA has a well‐established role in stress‐induced behaviors, and the CeL but not the CeM mediates relapse to methamphetamine self‐administration . Guanfacine increased CeL Arc immunoreactivity (Figure C,D), as seen previously, but nicotine‐treated groups showed decreased CeL activity overall.…”
Section: Discussionsupporting
confidence: 76%
“…There was a near‐significant decrease in BLA Arc immunoreactivity after guanfacine, which is consistent with previous research using in vivo electrophysiology and clonidine in the BLA . The CeA has a well‐established role in stress‐induced behaviors, and the CeL but not the CeM mediates relapse to methamphetamine self‐administration . Guanfacine increased CeL Arc immunoreactivity (Figure C,D), as seen previously, but nicotine‐treated groups showed decreased CeL activity overall.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, intracranial cannulas are implanted above the projection target region. To date, several studies have used local infusions of CNO into the projection target region to cause selective manipulation of only the DREADD‐expressing terminals in the target region (Lichtenberg et al ., ; Mahler et al ., ; McGlinchey and Aston‐Jones, ; Stachniak et al ., ; Venniro et al ., ). For example, Ge et al .…”
Section: Viral Methods For Chemogenetic Receptor Expressionmentioning
confidence: 97%
“…In addition, intracranial cannulas are implanted above the projection target region. To date, several studies have used local infusions of CNO into the projection target region to cause selective manipulation of only the DREADD-expressing terminals in the target region (Lichtenberg et al, 2017;Mahler et al, 2014;McGlinchey and Aston-Jones, 2017;Stachniak et al, 2014;Venniro et al, 2017). For example, Ge et al (2017) used this approach to show that inactivation of entorhinal cortex terminals in the dorsal dentate gyrus significantly decreased contextinduced reinstatement of heroin seeking.…”
Section: Circuit-specific Uses Of Chemogeneticsmentioning
confidence: 99%
“…Beyond its role in fear‐related behaviours, the amygdala has been shown to be involved in drug addiction (Makris et al., ; Wrase et al., ; Xie et al., ; Zill et al., ). Most notably, the central amygdala (CeA) has been reported as crucial for the incubation of craving for drugs such as nicotine, cocaine, morphine and methamphetamine (Funk et al., ; Li, Zeric, Kambhampati, Bossert, & Shaham, ; Li et al., ; Lu, Uejima, Gray, Bossert, & Shaham, ; Lu et al., ; Venniro et al., ). In recent studies, we have also shown that the CeA is involved in the development of compulsive choice of food and drug reward (Robinson, Warlow, & Berridge, ; Warlow, Robinson, & Berridge, ).…”
Section: Introductionmentioning
confidence: 99%